Determinants of Tier 2 Indian consumer's online shopping attitude: a SEM approach. Issue 6 (31st July 2019) - Kaur, Anupriya; Thakur, Preeti
Abstract : Purpose: The purpose of this paper is to validate the conceptual model that presents the determinants of Tier 2 consumer's online shopping attitude and the interrelationships among the constructs across the three Tier 2 cities in India. Design/methodology/approach: The paper uses survey-based data from three Tier 2 cities of North India – Kota, Agra and Jalandhar and uses a combination of statistical techniques to assess psychometric properties of the scales and conduct the measurement and structural invariance. Findings: The findings of the paper reveals that technology readiness, consumer innovativeness, fondness for branded products and perceived brand unavailability act as determinants of online shopping attitude and there is a positive relationship between online shopping attitude and online purchase intention among Tier 2 consumers in India while perceived offline hedonic value do not have any significant impact. Research limitations/implications: Future researchers can use this model with additional confidence given its cross-segment robustness. Practical implications: Online marketers can use the antecedents identified in this study to develop and encourage positive online shopping attitude in small town India. Originality/value: This research paper is the first one that investigated online shopping attitudes of Indian Tier 2 consumers. Importantly, it validated the determinants of online shopping attitude among Tier 2 consumers. National and international e-tailers aiming to develop and expand their operations to India now have the critical empirical verification concerned with the determinants of online shopping attitude and behaviour in India which would be meaningful to develop a sound marketing strategy.